Study on the Implementation of E-Government at the Village Level and Its Impact on Public Services - Panjaitan, Firta Sari; Batubara, Juliana; Sinta, Roma (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2025)
This study investigates the implementation of e-government at the village level and its impact on public service delivery. With the increasing integration of digital technologies in governance, understanding the effectiveness of e-government initiatives is crucial for enhancing citizen engagement and improving service efficiency. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess user satisfaction, service accessibility, and transparency in local governance. The findings reveal that e-government significantly enhances service efficiency, with reduced waiting times and streamlined processes, leading to increased user satisfaction. However, challenges such as the digital divide, data privacy concerns, and varying levels of digital literacy among residents present obstacles to full engagement. The study emphasizes the need for targeted investments in digital infrastructure and literacy programs to ensure equitable access to e-government services. By addressing these challenges, policymakers and local governments can harness the full potential of e-government to foster more inclusive and transparent public service delivery, ultimately strengthening community trust and engagement. This research contributes to the growing body of literature on e-government, providing insights into the dynamics of digital governance in rural contexts and highlighting best practices for effective implementation.